“Show that You Are a Woman”. Conflicts Connected with a Female-Partner’s Appearance in Polish-Russian Marriag - Busygina-Wojtas, Tatiana (Poznańskie Studia Slawistyczne, 2016)
Partners in Polish-Russian couples have different opinions concerning women’s appearence. Stressing femininity and paying much attention to attractiveness of a female-partner seems to be very important to Russian partners of both sexes. In this paper, this phenomenon is analyzed from two perspectives. The gender perspective pays special attention to the diversities in the evolution of partiarchal model in Poland and Russia. The analysis from the perspective of cultural anthropology leads to the conclusion about manifestation of Russian identity in Polish-Russian relations. Concidering “femininity” an important category and laying a metaphysical emphasis on it seems to be one of the ways of the “being Russian” manifestation.